Coupling Reaction of Aryl Halides with Orthoformate Ester - Shigemura, Saki; Kurahashi, Takuya (Synlett, 2024)
Herein, we report that orthoformate ester and N,N-dimethylformamide di-tert-butyl acetal can be a source of alkoxy radicals. We have developed a coupling reaction with aryl halides as a way of utilizing them. This has led to the synthesis of aromatic ethers with tertiary alkoxy groups, which are generally considered difficult to synthesize.
Keywords: C–O bond formation; hydrogen atom transfer; tertiary alkoxy group; photoredox reaction